Computer-Aided Construction and Evaluation of Poly-L-Lysine/Hyodeoxycholic Acid Nanoparticles for Hemorrhage and Infection Therapy - Qin Qin; Wenxing Wu; Ling Che; Xing Zhou; Diedie Wu; Xiaohui Li; Yumin Yang; Jie Lou (Pharmaceutics)
Background: Traumatic hemorrhage and infection are major causes of mortality in wounds caused by battlefield injuries, hospital procedures, and traffic accidents. Developing a multifunctional nano-drug capable of simultaneously controlling bleeding, preventing infection, and promoting wound healing is critical. This study aimed to design and evaluate a nanoparticle-based solution to address these challenges effectively. Methods: Using a one-pot assembly approach, we prepared a series of nanoparticles composed of poly-L-lysine and hyodeoxycholic acid (PLL-HDCA NPs). Theoretical simulations and experimental studies were combined to optimize their structure and functionality. In vitro platelet aggregation, antibacterial assays, cytotoxicity tests, and hemolysis evaluations were performed. In vivo efficacy was assessed in various hemorrhage models, a full-thickness skin defect model, and a skin irritation test. Results: PLL-HDCA NPs demonstrated effective induction of platelet aggregation and significantly reduced bleeding time and blood loss in mouse models, including tail vein, femoral vein, artery, and liver bleeding. Antibacterial assays revealed strong activity against E. coli and S. aureus. Wound healing studies showed that PLL-HDCA NPs promoted tissue repair in a full-thickness skin defect model. Cytotoxicity and hemolysis tests indicated minimal impact on human cells and significantly reduced hemolysis rates compared to PLL alone. Skin irritation tests confirmed the safety of PLL-HDCA NPs for external application. Conclusions: PLL-HDCA NPs represent a safe, efficient, and multifunctional nano-drug suitable for topical applications to control bleeding, combat infection, and facilitate wound healing, making them promising candidates for use in battlefield and hospital settings.